Enhancement of the anabolic effects of growth hormone and insulin-like growth factor I by use of both agents simultaneously. - Kupfer, S R (1993)
The use of growth hormone (GH) as an anabolic agent is limited by its tendency to cause hyperglycemia and by its inability to reverse nitrogen wasting in some catabolic conditions. In a previous study comparing the anabolic actions of GH and IGF-I (insulin-like growth factor I), we observed that intravenous infusions of IGF-I (12 micrograms/kg ideal body wt [IBW]/h) attenuated nitrogen wasting to a degree comparable to GH given subcutaneously at a standard dose of 0.05 mg/kg IBW per d. IGF-I, however, had a tendency to cause hypoglycemia. In the present study, we treated seven calorically restricted (20 kcal/kg IBW per d) normal volunteers with a combination of GH and IGF-I (using the same doses as in the previous study) and compared its effects on anabolism and carbohydrate metabolism to treatment with IGF-I alone. The GH/IGF-I combination caused significantly greater nitrogen retention (262 +/- 43 mmol/d, mean +/- SD) compared to IGF-I alone (108 +/- 29 mmol/d; P < 0.001). GH/IGF-I treatment resulted in substantial urinary potassium conservation (34 +/- 3 mmol/d, mean +/- SE; P < 0.001), suggesting that most protein accretion occurred in muscle and connective tissue. GH attenuated the hypoglycemia induced by IGF-I as indicated by fewer hypoglycemic episodes and higher capillary blood glucose concentrations on GH/IGF-I (4.3 +/- 1.0 mmol/liter, mean +/- SD) compared to IGF-I alone (3.8 +/- 0.8 mmol/liter; P < 0.001). IGF-I caused a marked decline in C-peptide (1,165 +/- 341 pmol/liter; mean +/- SD) compared to the GH/IGF-I combination (2,280 +/- 612 pmol/liter; P < 0.001), suggesting maintenance of normal carbohydrate metabolism with the latter regimen. GH/IGF-I produced higher serum IGF-I concentrations (1,854 +/- 708 micrograms/liter; mean +/- SD) compared to IGF-I only treatment (1,092 +/- 503 micrograms/liter; P < 0.001). This observation was associated with increased concentrations of IGF binding protein 3 and acid-labile subunit on GH/IGF-I treatment and decreased concentrations on IGF-I alone. These results suggest that the combination of GH and IGF-I treatment is substantially more anabolic than either IGF-I or GH alone. GH/IGF-I treatment also attenuates the hypoglycemia caused by IGF-I alone. GH/IGF-I treatment could have important applications in diseases associated with catabolism.